A improved group quantum key distribution protocol with multi-party collaboration - Qi Yuan; Hao Yuan; MeiTong Zhou; JingJing Wen; JuYan Li; Bing Hao (Scientific Reports)
Abstract The rapid advancement of quantum key distribution technology in recent years has spurred significant innovation within the field. Nevertheless, a crucial yet frequently underexplored challenge involves the comprehensive evaluation of security quantum state modulation. To address this issue, we propose a novel framework for quantum group key distribution. In the setup phase, preprocessing is introduced to monitor photon intensity and count, thereby ensuring the secure initialization of the protocol. During the measurement phase, signal consistency checks are implemented to verify that the intensity of the signal received by the measurement device corresponds precisely to the transmitted signal. In the key generation phase, error correction is employed to mitigate errors induced by noise or external interference, effectively reducing the error margin and restricting the information available to potential eavesdroppers. This systematic, multi-phase approach significantly enhances the framework’s robustness. Experimental results demonstrate that the proposed protocol not only substantially reduces the error rate under adversarial eavesdropping but also improves the efficiency and security of the key distribution process.